PEMANFAATAN TEKNOLOGI BLOCKCHAIN PADA PLATFORM CROWDFUNDING - Harahap, Eka Purnama; Aini, Qurotul; Anam, Reza Khaerul (Technomedia Journal, 2020)
Crowdfunding as a social program in the technological era is a new breakthrough for raising funds for people who need or to capitalize a particular project quickly through the internet media. This research aims to study the benefits of blockchain technology with the concept of smart contracts as a medium of transaction in a crowdfunding platform, as well as how this technology can solve the problem of public trust because this platform uses transactions that use money. By implementing blockchain technology on crowdfunding platforms, it is expected to guarantee data security and approval in each transaction, so that there is no falsification of a project for personal gain.